Of genes and drugs: genetic determinants of adverse drug reactions - Masellis, Mario (Henry Stewart Talks, 2007)
Type A and B Adverse Drug Reactions (ADRs), Pharmacokineticpharmacodynamic paradigm, ADME framework, Mechanisms of ADRs, Pharmacogenetics and pharmacogenomics, Polygenic traits, Environmental factors, Phenotype and endophenotype, Candidate genes, Association and linkage disequilibrium